Fostering Self-Awareness and Self-Regulation in English Speaking Skills through Metacognitive Strategies: A Qualitative Perspective - Ulfah Syam; Iskandar; Abdul Halim (Indonesian Journal Publisher, 2025)
This study investigates how metacognitive strategies foster self-awareness and self-regulation in English speaking among university students. Employing a qualitative research design, data were collected through classroom observations and semi-structured interviews with English language students to explore their experiences using planning, monitoring, and evaluating strategies to develop speaking skills. Findings show that applying metacognitive strategies enables students to effectively plan speech content, monitor language use in real-time, and reflect on performance for continuous improvement. Students reported increased confidence, clearer expression of ideas, and a heightened ability to identify personal strengths and weaknesses in speaking. Additionally, the study highlights the crucial role of guided instruction and supportive feedback from lecturers in enhancing learners’ metacognitive awareness and promoting autonomous learning behaviors. These results suggest that metacognitive strategy instruction serves as a powerful pedagogical tool for improving speaking proficiency and learner autonomy, underscoring its importance in English language education at the tertiary level.